Can Biden build back better? Yes, if he abandons fiscal "pay fors" - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2021)
President Biden's proposals for investing in social and physical infrastructure signal a return to a budget-neutral policymaking framework that has largely been set aside since the outbreak of the COVID-19 crisis. According Yeva Nersisyan and L. Randall Wray, this focus on ensuring revenues keep pace with spending increases can undermine the goals internal to both the public investment and tax components of the administration's plans: the "pay-for" approach limits our spending on progressive policy to what we can raise through taxes, and we will only tax the amount we need to spend. Nersisyan and Wray propose an alternative approach to budgeting for large-scale public expenditure programs. In their view, policymakers should evaluate spending and tax proposals on their own terms, according to the goals each is intended to meet. If the purpose of taxing corporations and wealthy individuals is to reduce inequality, then the tax changes should be formulated to accomplish that-not to "raise funds" to finance proposed spending. And while it is possible that general tax hikes might be needed to prevent public investment programs from fueling inflation, they argue that the kinds of taxes proposed by the administration would do little to relieve inflationary pressures should they arise. Under current economic circumstances, however, the president's proposed infrastructure spending should not require budgetary offsets or other measures to control inflation in their estimation.
Keywords: 330